Enhancing Tourism Development Strategies - Rafael Sarimurat; Hendri Koeswara; Isfarudi Isfarudi (Univiversitas Dr. Djar Wattiheluw, 2024)
This study evaluates the tourism marketing strategies of the Mentawai Islands government and examines key factors influencing its development. With rich cultural rituals, breathtaking landscapes, and world-class waves, the Mentawai Islands hold significant tourism potential that requires strategic management. Using qualitative methods and SWOT analysis, the research identifies exceptional waves as a strength, increasing tourist arrivals as an opportunity, low community awareness as a weakness, and inadequate service standards as a threat. To address these issues, the study suggests developing a comprehensive marketing strategy, establishing clear government regulations, enhancing public facilities and tourism personnel quality, and optimizing the region's resources to support sustainable growth.